Abdominal obesity and dsyglycemia are risk factors for liver fibrosis progression in NAFLD subjects: A population-based study - Julián, María Teresa; Ballesta, Sílvia; Pera, Guillem; Pérez-Montes de Oca, Alejandra; Soldevila, Berta; Caballería, Llorenç; Morillas, Rosa; Expósito, Carmen; Martínez–Escudé, Alba; Puig-Domingo, Manel; Franch-Nadal, Josep; Torán, Pere; et al. (Frontiers in Endocrinology, 2023)
Objective To investigate longitudinal changes in the liver stiffness measurement (LSM) in the general adult population without known liver disease and to describe its association with metabolic risk factors, with a special focus on subjects with non-alcoholic fatty liver disease (NAFLD) and dysglycemia. Material and Methods A longitudinal adult population-based cohort study was conducted in Catalonia. LSM was measured by transient elastography (TE) at baseline and follow-up (median: 4.2 years). Subgroup with NAFLD and dysglycemia were analyzed. Moderate-to-advanced liver fibrosis was defined as LSM ≥8.0 kPa and LSM ≥9.2 kPa respectively. Results Among 1.478 subjects evaluated, the cumulative incidence of LSM ≥8.0 kPa and ≥9.2 kPa at follow-up was 2.8% and 1.9%, respectively. This incidence was higher in NAFLD (7.1% for LSM ≥8.0 kPa and 5% for LSM ≥9.2 kPa) and dysglycemia (6.2% for LSM ≥8.0 kPa and 4.7% for LSM ≥9.2 kPa) subgroups. In the global cohort, the multivariate analyses showed that dysglycemia, abdominal obesity and atherogenic dyslipidemia were significantly associated with progression to moderate-to-advanced liver fibrosis. Female sex was negatively associated. In subjects with NAFLD, abdominal obesity and dysglycemia were associated with changes in LSM to ≥8.0 kPa and ≥9.2 kPa at follow-up. A decline in LSM value to <8 kPa was observed in 64% of those subjects with a baseline LSM ≥8.0 kPa. Conclusions In this population study, the presence of abdominal obesity and dysglycemia were the main risk metabolic factors associated with moderate-to-advanced liver fibrosis development over time in general populations as well as in subjects with NAFLD.